Maritime Employee rights - Dawood Salman, Lect. Murtaja (Basra studies journal, 2023)
Considering the privacy in which work at sea is distinguished from other work on land, because it requires that the worker be present on the ship throughout the duration of the sea voyage, which may take months, so it is necessary to regulate the wages that the worker deserves, how to calculate them, and his right to treatment if exposed For a health emergency during the voyage, as well as his right to food and food, and his right to return him to his homeland, especially since Iraq lacks legislation regulating these rights due to the absence of a maritime law regulating maritime work. Even the Ottoman Maritime Trade Law, which is an old law, the articles that regulate the work of maritime workers have been canceled according to Trade Act of 1943.